Efecto antimicrobiano in vitro del extracto etanólico hoja Aloe vera sobre Streptoccocus mutans ATCC 25175 - Lecca Rojas, Roberto Manuel (2020)
In the present study of the experimental type, it was intended to determine the in vitro antibacterial effect of the ethanolic extract of the Aloe vera leaf (Aloe Vera) against Streptococcus mutans. The susceptibility test was performed, to determine the minimum bactericidal concentration (CMB) the diameter of the inhibition halos formed in the Petri dishes was measured over the concentrations of 25%, 50% and 75% of the ethanolic extract of the Aloe leaf Vera and his control. All presented halos of inhibition in which there was proportionality (The diameter of the halo of inhibition is directly proportional to the concentrations used) To determine the Minimum Inhibitory Concentration, the tube dilution method was used, having the same concentrations and their control, each culture was seeded with Mueller Hinton-Blood Agar to determine the Colony Forming Units (CFUs).The results obtained for the Minimum Bactericidal Concentration (CMB) by measuring the inhibition halos when 25%, 50% and 75% of the ethanol extract of Aloe vera were used were 7. 6 mm, 10.7 mm and 13.5 mm respectively; and in the 45mm control group The results obtained for Minimum Inhibitory Concentration (MIC) measuring the turbidity of the tube and inoculating in Petri dishes with Mueller Hinton-Blood agar,25% colony growth of 0.9x102 CFU and not 50% and 75 %, the negative control group 2.8x105UFC´s and the positive control group or UFC´s. Finally, it is concluded that the ethanolic extract of the Aloe vera leaf does have in vitro antimicrobial activity on Streptococcus mutans.